2022
DOI: 10.1002/ird.2666
|View full text |Cite
|
Sign up to set email alerts
|

The effect of deficit irrigation, partial root drying and mulching on tomato yield, and water and energy saving*

Abstract: Partial root drying (PRD) is a modified irrigation strategy form of deficit irrigation (DI) to improve water productivity. The objective of this study was to investigate the effect of PRD, DI and organic mulching on water and energy conservation, as well as tomato yield. A field trial was carried out during the 2019 and 2020 summer seasons in Kafr El-Sheikh governorate, Egypt. The main plots were assigned for the irrigation treatments, full irrigation with 100% of crop evapotranspiration, ETc (I 1 ), deficit i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
(86 reference statements)
0
5
1
Order By: Relevance
“…This could be attributed to the stable tendency of yield from ET95 to ET225 (Figure 6b), in which increased irrigation rates played the dominant role in the change in WP. Compared to previous studies, the optimal DI levels for max WP appeared in the range of 50-100% ET [10][11][12][13][14]. The optimal DI scenario in this study (i.e., ET95) was also in this range.…”
Section: Optimizing Deficit Irrigation Management For Maximizing Yiel...contrasting
confidence: 49%
See 1 more Smart Citation
“…This could be attributed to the stable tendency of yield from ET95 to ET225 (Figure 6b), in which increased irrigation rates played the dominant role in the change in WP. Compared to previous studies, the optimal DI levels for max WP appeared in the range of 50-100% ET [10][11][12][13][14]. The optimal DI scenario in this study (i.e., ET95) was also in this range.…”
Section: Optimizing Deficit Irrigation Management For Maximizing Yiel...contrasting
confidence: 49%
“…Many studies focused on exploring the optimal DI managements without tomato WP penalties [9]. However, the optimal DI level ranged widely in most studies, e.g., 50% crop evapotranspiration (ET) [10], 70% ET [11], 75% ET [12], 80% ET [13] and 100% ET [14]. These different observations were mainly because, in addition to the DI levels, other factors also affected the yield change after DI adoption, e.g., tomato cultivars [15], soil types [16], local climate [17] and fertilizers [18].…”
Section: Introductionmentioning
confidence: 99%
“…Adequate irrigation and nitrogen application amount (T 5 ) produced the highest FDM and PDM in both years. Moderate irrigation and nitrogen levels could promote efficient water and nitrogen usage and vegetative and reproductive growth through the contribution of enzymes involved in nitrogen metabolism, and induce the growth of the lateral roots and increase root quality, which improved the absorption of water and nutrient in the root zone, thereby increasing tomato FDM [40,41] .…”
Section: Effects Of Water and Nitrogen On The Growth Performance Of C...mentioning
confidence: 99%
“…Deficit irrigation (DI), defined as the application of water below the evapotranspiration requirements, is a practical irrigation strategy to enhance water productivity. Using DI strategy, the crop is exposed to a mild drought stress level either during the whole growing period or during a particular growth stage [93]. Studies have reported that DI strategies present significant opportunities for conserving water without sacrificing crop yield, or with only a minor reduction in yield, while also improving the quality of the produce [94][95][96][97].…”
Section: Deficit Irrigation Effects On Productivity and Nutritional Q...mentioning
confidence: 99%